Exploring the Use of Gender-Fair Language by Influencers; [探究有影響力的人士如何使用性別中立語言] - Nicolas-Alarcon, C (Emerald Publishing, 2023)
Purpose: Explore the use of Gender-Fair Language (GFL) by influencers on Instagram. Design/methodology/approach: The clustering methodology. A digital Bag-of-Words (BoW) Method called GFL Clustering BoW Methodology to identify whether an inclusive marketing (IM) strategy can be used. Thus, this research has a methodological and practical contribution to increasing the number of marketing technology tools. Findings: This study is original as it proposes an inclusive digital marketing strategy and contributes with methods associated with digital transfers in order to improve marketing strategies, tactics and operations for inclusive content with a data integrity approach. Research limitations/implications: Due to the limitations of the application programming interface (API) of the social network Instagram, a limited number of text data were used, which allowed for retrieving the last 12 publications of each studied profile. In addition, it should be considered that this study only includes the Spanish language and is applied to a sample of influencers from Chile. Practical implications: The practical contribution of this study will lead to a key finding for the definition of communication strategies in both public and private organizations. Originality/value: The originality of this work lies in its attractive implications for nonprofit and for-profit organizations, government bodies and private enterprises in the measurement of the success of campaigns with an IM communicational strategy and to incorporate inclusive and non-sexist content for their consumers so as to contribute to society. © 2023, Carolina Nicolas, Angelica Urrutia and Gonzalo González.